The diversity and abundance of stray cat in Johor Bahru, Johor / Fatin Syafira Md Yusof, Sarah Shazwani Zakaria and Ting Kung Siang - Md Yusof, Fatin Syafira; Zakaria, Sarah Shazwani; Ting, Kung Siang (UiTM Cawangan Negeri Sembilan, 2022)
Cats (Felis catus) are one of the world's invasive species due to their close relations with human beings. Generally, stray cats are cats that were abandoned by their previous owners while feral cats are the ones that usually live in a colony away from human contact. The distribution and profile of the stray cats in Johor Bahru are unknown and need to be investigated. Thus, this study was conducted to determine the composition and abundance of stray cats in Taman Daya, Adda Heights, Taman Setia Indah, and Ulu Tiram. As well as to assess and compare the health conditions of the stray cats between localities. The stray cats' data were collected by using the mark-recapture technique and by counting and calculating the stray cats at the animal shelters visited. The stray cats were examined by the veterinarian to obtain their sex, breed, age, weight, temperature, reproduction status, and medical conditions. A total of 42 stray cats were caught and six breeds were identified, with Domestic Short Hair having the highest number of individuals. Then, the data were analyzed using PAST version 4.04 software indicated that Taman Daya has the highest diversity of stray cats with (H'=1.437) and breed richness with (R'=1.477) while Adda Heights has the highest evenness of stray cat breeds amongst the four locations with (E'=0.9806). Overall, this study shows the diversity (H') =1.504, richness (R') =1.355 and evenness (E') = 0.7500 of stray cats in these four locations, respectively which may acknowledge society about the diversity and abundance of stray cats and contribute towards controlling the number of stray cats. However, further in-depth studies are required to record more data of stray cats within this area.